"Big Brother" can watch us. (10th June 2016) - Power, Daniel J.
Abstract: Privacy, surveillance, and government abuse of data are concerns of many people in our complex digital world. 'Big Brother' in the title of this article is a metaphorical warning about the consequences if government uses modern technologies to maintain power and control people. Issues related to the abuse of data and surveillance are not new in the academic literature and mass market media, the current threat is however greater. Technology has advanced to the point where George Orwell's dystopian 'Big Brother' vision of a totalitarian state is possible. Because of technology advances, barriers associated with collecting and processing real-time data about many millions of individuals have been removed. This article explores how the capture and use of new data streams, and processing with AI and predictive analytics can support government control of its citizens. Some components of a system for thought control and real-time surveillance are already in use. These components like cameras, sensors, No SQL databases, predictive analytics, and artificial intelligence can be connected and improved. Decision support researchers must understand the issues and resist attempts to use information technologies to support current or future totalitarian governments.